A Fish Leukocyte Immune-Type Receptor Uses a Novel Intracytoplasmic Tail Networking Mechanism to Cross-Inhibit the Phagocytic Response - Fei, Chenjie (Int J Mol Sci, 2020)
Channel catfish (Ictalurus punctatus) leukocyte immune-type receptors (IpLITRs) are a family of immunoregulatory proteins shown to regulate several innate immune cell effector responses, including phagocytosis. The precise mechanisms of IpLITR-mediated regulation of the phagocytic process are not entirely understood, but we have previously shown that different IpLITR-types use classical as well as novel pathways for controlling immune cell-mediated target engulfment. To date, all functional assessments of IpLITR-mediated regulatory actions have focused on the independent characterization of select IpLITR-types in transfected cells. As members of the immunoglobulin superfamily, many IpLITRs share similar extracellular Ig-like domains, thus it is possible that various IpLITR actions are influenced by cross-talk mechanisms between different IpLITR-types; analogous to the paired innate receptor paradigm in mammals. Here, we describe in detail the co-expression of different IpLITR-types in the human embryonic AD293 cell line and examination of their receptor cross-talk mechanisms during the regulation of the phagocytic response using imaging flow cytometry, confocal microscopy, and immunoprecipitation protocols. Overall, our data provides interesting new insights into the integrated control of phagocytosis via the antagonistic networking of independent IpLITR-types that requires the selective recruitment of inhibitory signaling molecules for the initiation and sustained cross-inhibition of phagocytosis.